Application of Thealoz® duo eye drops confers novel protective effects on the ocular surface of dry eye patients - Perumal, Natarajan; Jeong, Eunjin; Runde, Sarah; Manicam, Caroline; Pfeiffer, Norbert; Grus, Franz (Acta ophthalmologica (Oxford, England), 2022)
Purpose: The protective effect of Thealoz® Duo eye drops was investigated in patients with dry eye syndrome (DES) by clinical examination. Subsequently, the tear proteome alterations were characterized employing the mass spectrometry‐based proteomics platform. Methods: Fifty‐eight subjects underwent thorough clinical investigation for DES, namely the ocular surface disease index (OSDI), and were grouped as mixed DES (DRY, N = 35) and healthy (CTRL, N = 23). A DRY subgroup of severe aqueous‐deficient DES (sDRYaq, N = 12) was also clinically identified. Only DES patients were subjected to application of Thealoz® Duo (trehalose 3% and hyaluronic acid 0.15%). All subjects were scheduled for clinical investigation before (day 0, T0) and after day 28 ± 4 (T28) and 56 ± 4 (T56) of Thealoz® Duo application. Next, 174 individual tear samples from both groups at two time‐points were subjected to in‐depth proteomics and bioinformatics analyses. Results: Application of Thealoz® Duo (4.2 ± 0.9 times/day) significantly improved the OSDI in DRY at T28 vs. T0 (p = 4.1 E‐3) and T56 vs. T0 (p = 2.0 E‐5). Proteomics analysis resulted in the identification of 128 and 291 significantly (p < 0.05) differently abundant proteins in DRY vs. CTRL and sDRYaq vs. CTRL, respectively. Interestingly, Thealoz® Duo application after only T28 resulted in significant activation of various molecular processes, mainly the antibacterial response (DRY vs. CTRL, p = 2.3 E‐4; sDRYaq vs. CTRL, p = 5.7 E‐5), metabolic pathways (DRY vs. CTRL, p = 4.9 E‐3; sDRYaq vs. CTRL, p = 4.7 E‐6) and inhibition of apoptosis (DRY vs. CTRL, p = 4.1 E‐4; sDRYaq vs. CTRL, p = 8.9 E‐17). Importantly, the activated inflammatory process at T0 in DRY (p = 9.7 E‐4) and sDRYaq (p = 2.0 E‐8) were significantly inhibited at T56 following the continuous use of Thealoz® Duo. Conclusions: For the first time, this comprehensive investigation unravelled novel mechanistic processes attributed to the efficacy of Thealoz® Duo eye drops, which significantly improved vision‐related functions in mixed and severe DES patients.